EFFECT OF POST THAW INCUBATION ON QUALITY OF FROZEN THARPARKAR BULL SEMEN - KEDIA, N K; TIWARl, R P; MISHRA, G K; AWASTHl, M K; SAHU, S B (The Indian Journal of Animal Reproduction, 2023)
The period spent after thawing and before insemination may affect the quality and fertility of post thaw semen. The frozen semen was thawed at 37°C for 30 seconds and taken into a small sugar tube and incubated in the water bath at 37°C for 0, 15, 30, 45 and 60 min and post thaw motility (PTM % ), hypo osmotic swelling test (HOST%) and cervical mucus penetration test (CMPT -mm/60 min) were carried out. The mean (range) of PTM observed at respective intervals was 52.22 ± 1.09 (45-60), 51.39 ± 0.97 (45-60), 46.94 ± 0.59 (45-50), 40.28 ± 0.85 (35-45) and 32.22 ± 0.92 (25-40) %. The corresponding values of HOST were 54.39 ± 2.54 (30-71), 51.28 ± 1.79 (40-65), 44.77 ± 1.87 (32-58), 34.17 ± 1.49 (23-43) and 24.50 ± 1.10 (16-32) % and CMPT 29.39 ± 1.16 (22-40), 27.78 ± 0.92 (23-36), 23.11 ± 0.81 (19-31 ), 16.39 ± 0.16 (12-24) and 10.28 ± 0.54 (7-15) mm/60min. The overall post thaw motility at 0, 15 and 30 min was found to. be significantly higher (P<0.01) than 45 and 60 min in Tharparkar bulls, however overall HOST and CM PT were significantly higher (P<0.01) at O and 15 min than at 30, 45 and 60 min. Post thaw motility remained unaffected up to 30 min post thaw incubation while there was significant decline in HOS reactive sperm and cervical mucus penetration at 30, 45 and 60 min which indicated that motility may remain good but increasing post thaw incubation duration affects cell membrane permeability and cervical mucus penetration ability of spermatozoa which may affect fertility.